2018
DOI: 10.17240/aibuefd.2018..-412111
|View full text |Cite
|
Sign up to set email alerts
|

2018 Fen Bi̇li̇mleri̇ Öğreti̇m Programi Kazanimlarindaki̇ Deği̇şi̇mler Ve Fen Teknoloji̇ Matemati̇k Mühendi̇sli̇k (Stem) Entegrasyonu

Abstract: Bu araştırmanın amacı, i) 2017-2018 eğitim öğretim yılı başında 5. sınıfta pilot olarak uygulanan ve daha sonra güncellenerek 2018 Ocak ayında revize edilen 3-8. Sınıflar Fen Bilimleri öğretim programları arasındaki farkı STEM açısından ortaya koymak, ii) güncellenen 2018 fen bilimleri öğretim programında 2013 fen bilimleri öğretim programına kıyasla ünitelere ilişkin kazanımlar ve kazanımlar için ayrılan sürelerin ne şekilde değiştiğini belirlemek ve iii) 2018 fen bilimleri öğretim programında STEM'e ilişkin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 26 publications
2
13
0
6
Order By: Relevance
“…This is a significant example supporting the argument that the curriculum intensity was decreased. Similar results have been obtained in various studies (Bahar, Yener, Yılmaz, Emen and Gürer, 2018).…”
Section: Published By Sciedu Presssupporting
confidence: 92%
“…This is a significant example supporting the argument that the curriculum intensity was decreased. Similar results have been obtained in various studies (Bahar, Yener, Yılmaz, Emen and Gürer, 2018).…”
Section: Published By Sciedu Presssupporting
confidence: 92%
“…Similarly, Şahin (2013) stated that students' interest in STEM fields increased with participation in STEM activities related to real life. It is considered that students with learning experiences based on STEM education are individuals who can solve problems, are innovative, have high self-confidence, think logically, and are science and mathematics literate, in addition to reaching capacity in careers related to the science fields (Bahar, Yener, Yılmaz, Emen, & Gürer, 2018).…”
Section: Stem Educationmentioning
confidence: 99%
“…Current research has revealed the need for science education, including many disciplines within its nature and based on research/questioning, enriched with engineering design approaches (Topalsan, 2018). "Acting as a bridge between engineering, science and mathematics-based theories and technology used, with the aim of resolving social requirements, and acting to integrate scientific principles and mathematical theories, it is emphasized that engineering design-based approaches have great importance for the development of science education" (Bahar et al, 2018).…”
Section: Engineering Designmentioning
confidence: 99%
“…Fen bilgisi öğretmen adaylarının da bu akımdan etkilenerek mühendislik ve tasarım becerilerine ilgi duydukları ve bu konudaki gelişmeleri takip ettikleri söylenebilir. Bu noktada, daha önceki öğretim programlarında olmayan ancak 2018 yılındaki Fen Bilimleri Dersi Öğretim Programı'nda ilk defa yer alan mühendislik ve tasarım becerilerine (Bahar, Yener, Yılmaz, Emen ve Gürer, 2018) zihin haritalarında yer verilmiş olması programı uygulayacak olan öğretmen adayları için olumlu olarak değerlendirilmektedir.…”
Section: Sonuç Ve Tartışmaunclassified